Dystonia Management: What to Expect From the Future? The Perspectives of Patients and Clinicians Within DystoniaNet Europe - Smit, Marenka; Albanese, Alberto; Benson, Monika; Edwards, Mark J.; Graessner, Holm; Hutchinson, Michael; Jech, Robert; Krauss, Joachim K.; Morgante, Francesca; Pérez Dueñas, Belen; Reilly, Richard B.; Tinazzi, Michele; et al. (Frontiers in Neurology, 2021)
Improved care for people with dystonia presents a number of challenges. Major gaps in knowledge exist with regard to how to optimize the diagnostic process, how to leverage discoveries in pathophysiology into biomarkers and how to develop an evidence base for current and novel treatments. These challenges are made greater by the realisation of the wide spectrum of symptoms and difficulties faced by people with dystonia which go well beyond motor symptoms. A network of clinicians, scientists and patients could provide resources to facilitate information exchange at different levels, share mutual experiences, and support each other’s innovative projects. In the past, collaborative initiatives have been launched, including the American Dystonia Coalition, the European Cooperation in Science and Technology (COST - which however only existed for a limited time) and the Dutch DystonieNet project. The European Reference Network on Rare Neurological Diseases includes dystonia among other rare conditions affecting the central nervous system in a dedicated stream. Currently, we aim to broaden the scope of these initiatives to a comprehensive European level by further expanding the DystoniaNet network, in close collaboration with the ERN-RND. In line with the ERN-RND, the mission of DystoniaNet Europe is to improve care and quality of life for people with dystonia by, among other endeavours, facilitating access to specialized care, overcoming the disparity in education of medical professionals, and serving as a solid platform to foster international clinical and research collaborations. In this review, both professionals within the dystonia field and patients and care-givers representing Dystonia Europe, highlight important unsolved issues and promising new strategies, and the role that a European network can play in activating them.